Public perspectives on communication disorders and profession of speech-language pathology. (3rd July 2019) - Chu, Shin Ying; Tang, Keng Ping; McConnell, Grace; Mohd Rasdi, Hanif Farhan; Yuen, Man-Ching
ABSTRACT: This study aimed to investigate the knowledge and attitudes toward communication disorders and speech-language pathology among the general public in Malaysia. A self-developed questionnaire consisting of items related to knowledge and attitudes about communication disorders and speech-language pathology was distributed via Google form and a paper-pencil format. A total of 535 responses were obtained. Descriptive analyses based on the comparison of the demographics to the knowledge and attitude levels were conducted using inferential statistics. More than half of the respondents showed a moderate knowledge level about communication disorders and a high knowledge about speech-language pathology. In terms of attitudes, 67.3% of the respondents perceived a positive attitude towards people with communication disorders, and 86.5% of them were generally positive regarding the profession of speech-language pathology. Health professionals demonstrated a higher knowledge level and more positive attitudes toward communication disorders and speech-language pathology compared to other professions (teachers/services, business, engineers, and jobless/retired). Additionally, respondents with a higher educational level (masters or Ph.D. holders) had greater knowledge about speech-language pathology and more positive attitudes toward communication disorders compared to those who were primary or secondary school graduates. Providing more education and awareness programs about communication disorders and speech-language pathology to the general public should be implemented to improve current practices and expectations in service delivery.